2012
DOI: 10.1039/c1sc00232e
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of salt effects on carbon nanotube dispersions in an organic solvent (N-methyl-2-pyrrolidone)

Abstract: We consider the effects of salt (sodium iodide) on pristine carbon nanotube (CNT) dispersions in an organic solvent, N-methyl-2-pyrrolidone (NMP). We investigate the molecular-scale mechanisms of ion interactions with the nanotube surface and we show how the microscopic ion-surface interactions affect the stability of CNT dispersions in NMP. In our study we use a combination of fully atomistic Molecular Dynamics simulations of sodium and iodide ions at the CNT-NMP interface with direct experiments on the CNT d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 65 publications
2
23
1
Order By: Relevance
“…We measured the CCC for NaBr in a NMP SWCNT dispersion, quiescent and in the dark, to be 5.5 AE 0.5 mM. This is consistent with similar studies of NaI in NMP during agitation by Frolov et al 58 Their work reports a qualitative description of dispersion stability consistent with what we have reported quantitatively for the NaBr, 31 and other inorganic salts. 59 In this paper we quantify the dispersion stability, X o , of SWCNTs in DMF and measure the slow RLCA kinetics of a homologous series of ruthenium complexes as a function of charge state and binding capabilities of the coagulant.…”
Section: Dispersion Stabilitysupporting
confidence: 91%
“…We measured the CCC for NaBr in a NMP SWCNT dispersion, quiescent and in the dark, to be 5.5 AE 0.5 mM. This is consistent with similar studies of NaI in NMP during agitation by Frolov et al 58 Their work reports a qualitative description of dispersion stability consistent with what we have reported quantitatively for the NaBr, 31 and other inorganic salts. 59 In this paper we quantify the dispersion stability, X o , of SWCNTs in DMF and measure the slow RLCA kinetics of a homologous series of ruthenium complexes as a function of charge state and binding capabilities of the coagulant.…”
Section: Dispersion Stabilitysupporting
confidence: 91%
“…It was reported that the local structure of ionic liquid or organic solvent in a confined nanospace is substantially different from that in the bulk. [8][9][10] Recently, we have revealed experimentally and theoretically that the surface-induced hydration structure of platinum complex ions has large effects on the enhancement of platinum deposition within nanoporous a) Electronic mail: fukami.kazuhiro.2u@kyoto-u.ac.jp. b) Present address: Department of Energy and Hydrocarbon Chemistry, Graduate School of Engineering, Kyoto University, Nishikyo-ku, Kyoto 615-8510, Japan.…”
Section: Introductionmentioning
confidence: 99%
“…1(a) shows the photo images of the MWCNTs (as received) and f-CNTs (after functionalization) in the PEI/NMP/DMF dope solution. The f-CNTs could well disperse in the solution while this phenomenon was not observed for the MWCNTs, presumably due to the polar-polar affinity and electrostatic repulsion of the -COOH on f-CNTs [33,34,38,39].…”
Section: Characterization Of F-cntsmentioning
confidence: 75%